Robotic hand controlled by hand gesture - Nawwas, Mutaz; Rajab, Amr (My University, 2017)
The name of our project is " Robotic hand controlled by hand gesture " , it a robotic hand that can receive command from hand gesture , so that when you move your hand the robotic hand will make the same move . The basic components of the project are the glove , the robotic hand , flex sensors , Ardunio and any type of wireless connection . The glove will be mounted with flex sensors , the Arduino reads the voltage change when sensors are bent and sends data by wireless to the other Arduino that will trigger the servos to move . The servos pull strings allowing the fingers and other part of hand to move . we will build the robotic hand from scratch , so that we will use wood to build the structure of hand and we will make Iron joints for fingers and arm .